Changes in electrocardiogram parameters during acute nonshivering cold exposure and associations with brown adipose tissue activity, plasma catecholamine levels, and brachial blood pressure in healthy adults - Raiko Juho; Saari Teemu; Orava Janne; Savisto Nina; Parkkola Riita; Haaparanta-Solin Merja; Nuutila Pirjo; Virtanen Kirsi (WILEY, 2022)
Background: Sympathetic activity causes changes in electrocardiogram (ECG) during cold exposure and the changes have been studied mostly during hypothermia and less during mild acute nonshivering cold exposure. Cold-induced sympathetic activity also activates brown adipose tissue (BAT) and increases arterial blood pressure (BP) and plasma catecholamine levels. We examined changes in ECG parameters during acute nonshivering cold exposure and their associations with markers of sympathetic activity during cold exposure: brachial blood pressure (BP), plasma catecholamine levels, and BAT activity measured by positron emission tomography (PET).Methods and results: Healthy subjects (M/F = 13/24, aged 20-55 years) were imaged with [O-15]H2O (perfusion, N = 37) and [F-18]FTHA to measure plasma nonesterified fatty acid uptake (NEFA uptake, N = 37) during 2-h nonshivering cold exposure. 12-lead ECG (N = 37), plasma catecholamine levels (N = 17), and brachial BP (N = 31) were measured at rest in room temperature (RT) and re-measured after a 2-h nonshivering cold exposure. There were significant differences between RT and cold exposure in P axis (35.6 +/- 26.4 vs. 50.8 +/- 22.7 degrees, p = 0.005), PR interval (177.7 +/- 24.6 ms vs.163.0 +/- 28.7 ms, p = 0.001), QRS axis (42.1 +/- 31.3 vs. 56.9 +/- 24.1, p = 0.003), and QT (411.7 +/- 25.5 ms vs. 434.5 +/- 39.3 ms, p = 0.001). There was no significant change in HR, QRS duration, QTc, JTc, and T axis during cold exposure. Systolic BP (127.2 +/- 15.7 vs. 131.8 +/- 17.9 mmHg, p = 0.008), diastolic BP (81.7 +/- 12.0 vs. 85.4 +/- 13.0 mmHg, p = 0.02), and plasma noradrenaline level increased during cold exposure (1.97 +/- 0.61 vs. 5.07 +/- 1.32 mu mol/L, p = 0.001). Cold-induced changes in ECG parameters did not correlate with changes in BAT activity, brachial BP, plasma catecholamines, or skin temperature.Conclusions: During short-term nonshivering cold exposure, there were increases in P axis, PR interval, QRS axis, and QT compared to RT in healthy adults. Cold-induced changes in ECG parameters did not correlate with BAT activity, brachial BP, or plasma catecholamine levels which were used as markers of cold-induced sympathetic activity.